Elaboration of a Dehydrated Pineapple (Ananas comosus) Snack by Osmo-convection - Moreira H., Izza F. (Zamorano: Escuela Agrícola Panamericana, 2025)
Dehydration is a crucial food preservation technique that enhances shelf life and nutritional quality of perishable products. This study explored the production of a pineapple snack using osmo-convective dehydration. In the context of increasing demand for healthier snacks, osmotic dehydration offers an alternative to preserve tropical fruits while maintaining their nutrient profile. The research applied various osmotic treatments with immersion times of 6, 12, and 24 hours in a honey-water-lime solution prior to drying which were compared to convective drying with no immersion (control). Physicochemical properties (water activity, texture, dietary fiber content, and yield) were analyzed alongside sensory evaluations to assess consumer acceptance and preference. Results showed that immersion significantly improved the texture, and nutritional profile of the dehydrated snack. Water activity of all treatments was below 0.60 and, as immersion times increased, water activity was reduced below 0.50, leading to shelf stable products with reduced risk of microbial growth. Yields increased (33-41%) when immersion was conducted while color hue and luminosity were reduced. Sensory evaluations indicated moderated positive consumer acceptance for all treatments, particularly for flavor and texture of the snacks. In terms of preference, panelists chose the dehydrated pineapple with six hours of immersion over the control and this treatment resulted in 2 grams of dietary fiber per portion (20 g) making it a source of this nutrient. These findings suggested that osmo-convective dehydration can effectively enhance the quality and shelf life of pineapple snacks, making them a promising alternative for promoting healthier dietary habits.